Caribbean Report 21-05-1999 - The British Broadcasting Corporation; Richards, Ken (anchor, correspondent); Gordon, Orin (correspondent); Lara, Brian (interviewee); Greenidge, Gordon (interviewee); Hughes, Hubert (interviewee); Banks, Victor (interviewee); Jarvis, Mike (correspondent); Shillingford, Henry (interviewee); Smith, Lew (correspondent) (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Ken Richards (00:22) 2. Orin Gordon reports from Dublin, Ireland where the West Indies won their match against Bangladesh to keep their chances alive in the World Cup. Team captain Brian Lara and Gordon Greenidge analyse the match results (00: 23 – 05: 19) 3. In Anguilla two members of coalition government Finance Minister Victor Banks, and Social Services Edison Baird are scheduled to resign over dissatisfaction with Chief Minister Hubert Hughes leadership. Minister Hubert Hughes discusses the breakdown of the coalition and the effects on the political climate in Anguilla. Victor Banks discusses his resignation (05:20 - 9:00) 4. In elections in Dutch Sint Maarten officials anticipate a turnout of seventy percent. Mike Jarvis reports on the voting process (09:01 - 11:29) 5. Guyana’s President Janet Jagan is in Brazil on a mission to expand trade and improve regional relationship with the country. Other agenda issues include commerce, import of food and livestock, drug trans-shipment and illegal mining (11: 30 – 12: 59) 6. At the meeting of the International Anti Whaling Commission Programme Director of the Dominica Conservation Association Henry Shillingford discusses the whaling industry as a viable revenue earner. Lew Smith reports (12:60 – 14:29) 7. Orin Gordon reports on the West Indies team participating in the World Cup Series (14:30 - 15:26)